Assessment Of Damage Index For Reinforced Concrete Frames Subjected To Seismic Excitations - Bashah, Siti Fatin Qhalilah Osman (Universiti Sains Malaysia, 2017)
In this study, the main objective is to develop fragility curve of regular moment-resisting frame based on different types of structural height, and ground motion records. 3 sets of concrete were used in this study and varied in terms of heights which are 3-, 6- and 9-storey for regular frame. Each structure frames was designed based on Eurocode 2 and 3 with the aid Eurocode 8 for earthquake loading. The SAP2000 and ETABS were used as the main tool to carry out the analysis. A pushover analysis (POA) was performed to get the performance of the structure due to static load. Triangular load was used to produce base shear-drift relationship. Then, an incremental dynamic analysis (IDA) was carried out with 3 ground motion records. While to develop the fragility curve, the result from IDA will be used as the main parameters. The IDA curves were compared with five level of performance level from Xue et al. (2008) study which are operation phase (OP), immediate occupancy (IO), damage control (DC), life safety (LS), and collapse prevention (CP). On the basis of the result of this thesis, it can be concluded that from POA result showed regular frames demonstrate a higher demand compared to irregular frames for concrete and steel frames. From the outcomes, it was proven that low-rise frame doesn’t achieve 1g of PGA at LS of limit state compared to mid and high-rise frame. Based on relationship between Damage Index and Damage State, the low-rise and mid-rise frame having minor damage compared to high-rise frame that having damage and should be repair. Furthermore, for the Fragility Curve, high-rise frame showed a higher probability of reaching and exceeding the performance level compared to mid-rise frame.